Types and Functions of English Code-Mixing in Maudy Ayunda’s YouTube Channel - Meisya, Adinda; Hanif, Diandra Mutiara; Rahmadiah, Intan (Cipta Pustaka Nusantara, 2025)
Sociolinguistics is a branch of linguistics that examines the relationship between society and language. When elements of one language are combined with another, the phenomenon is referred to as code-mixing. Maudy Ayunda, a well-known Indonesian artist, frequently employs code-mixing in several of her videos on her official YouTube Music channel. This study aimed to analyze the types of code-mixing used in her content. A descriptive qualitative method was employed, with data collected through documentation and note-taking. Hoffman’s framework was applied to categorize the types of code-mixing, while Sudijono’s formula was used to calculate their frequency. The findings revealed twenty-three instances of code-mixing. The most dominant type was intra-sentential code-mixing, with 15 occurrences (65.2%), followed by intra-lexical code-mixing with 6 occurrences (26.1%), and code-mixing involving a change in pronunciation with 2 occurrences (8.7%). These results indicate that intra-sentential code-mixing is the most prevalent strategy in Maudy Ayunda’s YouTube videos, while phonological code-mixing appears less frequently. The implications of this study suggest that digital platforms, such as YouTube, play a significant role in promoting linguistic hybridity in Indonesia. The frequent use of English code-mixing by a popular public figure not only demonstrates her bilingual competence but also influences audience perceptions of global identity and language prestige. This highlights how code-mixing in online popular culture may contribute to shaping linguistic practices among younger generations and provides meaningful insights for further sociolinguistic research on language use in digital media.